Inter- and intraspecific variation of chloroplast mini- and microsatellites DNA in the four closed related Acacia species - AYPBC Widyatmoko; Susumu Shiraishi (Universitas Gadjah Mada, 2014)
Mini- and microsatellites of four Acacia species, A. aulacocarpa, A. auriculiformis, A. crassicarpa and A.mangium were investigated on four non-coding regions of cpDNA, the intron of trnL, and the intergenicspacers of trnL - trnP, trnD - trnY, and trnP – trnW. Nine single base substitutions and six informative miniandmicrosatellites were detected in the the four cpDNA non-coding regions. Based on the substitutionsand mini- and microsatellites, ten cpDNA haplotypes (A - J) could be distinguished. Acacia auriculiformispossessed fi ve haplotypes, A. aulacocarpa, four haplotypes, and A. crassicarpa, three haplotypes. All samplesof A. mangium possessed the same haplotype. Mini- and microsatellites recognized in this study can beused for species identifi cation of the four Acacia species. The ten haplotypes could divided the four speciesinto 2 groups, A. aulacocarpa-A.crassicarpa group and A. auriculiformis-A. mangium group. By developing thePCR-based markers based on the sequence information, many experiments can be carried out for the Acaciaimprovement programs.